Cystic fibrosis of pancreas and nephrotic syndrome: a rare association - Selvi Kelekçi; Müsemma Karabel; Aydın Ece; Velat Şen; Ali Güneş; İlyas Yolbaş; Cahit Şahin (Korean Pediatric Society, 2013)
Cystic fibrosis (CF) is a genetic disease with autosomal recessive inheritance and is common in Caucasian people. The prevalence of this disease is between 1/2,000 and 1/3,500 live births, and the incidence varies between populations. Although the CF transmembrane conductance regulator gene is expressed in the kidneys, renal involvement is rare. With advances in the treatment of CF, life expectancy has increased, and some previously unobserved disease associations are now seen in patients with CF. It is important to follow patients with CF for possible abnormalities that may accompany CF. In this paper, we present two rare cases of CF accompanied by nephrotic syndrome.